2022
DOI: 10.1002/anie.202207580
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Life Aqueous Organic Redox Flow Batteries Enabled by Amidoxime‐Functionalized Ion‐Selective Polymer Membranes

Abstract: Redox flow batteries (RFBs) based on aqueous organic electrolytes are a promising technology for safe and cost-effective large-scale electrical energy storage. Membrane separators are a key component in RFBs, allowing fast conduction of charge-carrier ions but minimizing the cross-over of redox-active species. Here, we report the molecular engineering of amidoxime-functionalized Polymers of Intrinsic Microporosity (AO-PIMs) by tuning their polymer chain topology and pore architecture to optimize membrane ion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 41 publications
(1 reference statement)
0
39
0
Order By: Relevance
“… [5] In addition, modification of the nitrile groups of PIM‐DBMP to amidoxime (AO) substituents, [20] to give PIM‐DBMP‐AO, via reaction with hydroxylamine (Scheme 2), provided solubility in the polar aprotic solvent N ‐methyl‐2‐pyrrolidone (NMP). It was recently reported that PIM‐DBMP‐AO shows promise as an ionic transport membrane for redox flow batteries [21] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [5] In addition, modification of the nitrile groups of PIM‐DBMP to amidoxime (AO) substituents, [20] to give PIM‐DBMP‐AO, via reaction with hydroxylamine (Scheme 2), provided solubility in the polar aprotic solvent N ‐methyl‐2‐pyrrolidone (NMP). It was recently reported that PIM‐DBMP‐AO shows promise as an ionic transport membrane for redox flow batteries [21] …”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that PIM-DBMP-AO shows promise as an ionic transport membrane for redox flow batteries. [21] Details of the physical properties of each polymer are provided in Table 1. The copolymer PIM-DBMP 0.75 was only soluble in quinoline.…”
Section: Resultsmentioning
confidence: 99%
“…Designing ion-selective membranes with ordered ion transport channels has attracted significant interests in recent years 9 . Typical strategies include synthetic polymers with precise chain lengths and chain microstructures 10 , metal-organic framework 11 and covalent-organic frameworks with ordered ion channels 12 , or high-free-volume polymers with intrinsic micropores 13 16 . These synthetic membranes with subnanometer-sized channels facilitate vehicular transport and enhance ionic conductivity, however, the membrane selectivity can be compromised in concentrated electrolyte solutions due to weakened Donnan exclusion 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Polymers of intrinsic microporosity (PIMs) are solution-processable microporous materials with subnanometer channels generated from the inefficient packing of the rigid, contorted polymer chains. , PIMs have shown great promise as next-generation membrane materials for molecular separations, batteries, and fuel cells . We anticipate that if incorporated with redox-active structural units, PIMs with fast ion-transport channels could be used as high-performance electrode materials in electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%